PENERAPAN MODEL THINK TALK WRITE (TTW) DALAM PEMBELAJARAN MENULIS CERITA FANTASI PADA SISWA KELAS VII - Ani Rusmini; Wikanengsih Wikanengsih; Via Nugraha (IKIP Siliwangi, 2022)
Â This research is motivated by an increase in student learning outcomes towards the selection of learning models that are attractive and in accordance with student characteristics, and can measure the effectiveness of learning models, and student responses regarding the application of learning models. Especially in learning to write which is still difficult to master, and it requires continuous practice. The purpose of this study was to determine student learning outcomes by applying the think talk write model in learning to write fantasy stories, and student responses to the application of the thik talk write model. This study uses a qualitative descriptive method, with research techniques tests, observation, and interviews. The sample of this research is students of class VII-A MTS Darul Ma'arif, as many as 25 students. The results of student acquisition, from the pretest results with the highest score of 77, the lowest score of 40, the average pretest score of 62.56. Ten out of twenty-five students scored> 75 above the KKM score. While the postest score of the highest score is 95, the lowest score is 65 and the average postest score is 83.48. Twenty-two out of twenty-five students scored> 75 above the KKM score determined by the school. It can be concluded from the results of the posttest scores obtained an increase in student learning outcomes, on learning to write fantasy stories after using the think talk write model, with an average postest score of 83.48 which is superior. So the application of the think talk write model is declared effective and successful, and gets good responses from students.